Detecting the Activation of a Self-Healing Mechanism in Concrete by Acoustic Emission and Digital Image Correlation - E. Tsangouri; D. G. Aggelis; K. Van Tittelboom; N. De Belie; D. Van Hemelrijck (The Scientific World Journal)
Autonomous crack healing in concrete is obtained when encapsulated healing agent is embedded into the material. Cracking damage in concrete elements ruptures the capsules and activates the healing process by healing agent release. Previously, the strength and stiffness recovery as well as the sealing efficiency after autonomous crack repair was well established. However, the mechanisms that trigger capsule breakage remain unknown. In parallel, the conditions under which the crack interacts with embedded capsules stay black-box. In this research, an experimental approach implementing an advanced optical and acoustic method sets up scopes to monitor and justify the crack formation and capsule breakage of concrete samples tested under three-point bending. Digital Image Correlation was used to visualize the crack opening. The optical information was the basis for an extensive and analytical study of the damage by Acoustic Emission analysis. The influence of embedding capsules on the concrete fracture process, the location of capsule damage, and the differentiation between emissions due to capsule rupture and crack formation are presented in this research. A profound observation of the capsules performance provides a clear view of the healing activation process.